A Synthesis of Blue Carbon Stocks, Sources, and Accumulation Rates in Eelgrass (Zostera marina) Meadows in the Northeast Pacific. Issue 2 (28th January 2020) - Prentice, C.; Poppe, K. L.; Lutz, M.; Murray, E.; Stephens, T. A.; Spooner, A.; Hessing‐Lewis, M.; Sanders‐Smith, R.; Rybczyk, J. M.; Apple, J.; Short, F. T.; Gaeckle, J.; et al.
Abstract: There is increasing urgency to implement climate change mitigation strategies that enhance greenhouse gas removal from the atmosphere and reduce carbon dioxide (CO2 ) emissions. Recently, coastal "blue carbon" habitats⁠—mangroves, salt marshes, and seagrass meadows—have received attention for their ability to capture CO2 and store organic carbon (OC), primarily in their sediments. Across habitat types and regions, however, information about the sequestration rates and sources of carbon to local sediments remains sparse. Here we compiled recently obtained estimates of sediment OC stocks and sequestration rates from 139 cores collected from temperate seagrass ( Zostera marina ) meadows in Alaska, British Columbia, Washington, and Oregon. Across all cores sediment OC content averaged 0.75%. Organic carbon stocks in the top 25 cm and 1 m of the sediment averaged 1, 846 and 7, 168 g OC m −2, respectively. Carbon sequestration rates ranged from 4.6 to 93.0 g OC m −2 yr −1 and averaged 24.8 g OC m −2 yr −1 . Isotopic data from this region suggest that OC in the sediments is largely from noneelgrass sources. In general, these values are comparable to those from other temperate Z. marina meadows, but significantly lower than previously reported values for seagrasses globally. These results further highlight the need for local and species‐level quantification of blue carbon parameters. While temperate eelgrass meadows may not sequester and store as much carbon as seagrass meadows elsewhere, climate policy incentives should still be implemented to protect existing sediment carbon stocks and the other critical ecosystem services associated with eelgrass habitats. Plain Language Summary: As we search for innovative solutions to capture and store atmospheric carbon, coastal wetlands are doing so for free and at rates greater than mature forests. The carbon market, by brokering carbon offset monies, can fund coastal wetland restoration projects where a net greenhouse gas reduction can be shown. Yet seagrass carbon sequestration capacity varies among species and even within meadows of the same species. Thus, obtaining site‐specific carbon storage values is essential for restoration planning. Here we report carbon stocks and sequestration rates compiled from 30 eelgrass meadows ( Zostera marina ) in Oregon, Washington, British Columbia, and Alaska, areas underrepresented in current literature. We then compare these findings to previously reported values for Z. marina and for seagrasses globally. While carbon stocks and sequestration rates varied at small spatial scales, we observed no latitudinal patterns. Our values were similar to those found in other Z. marina meadows, but significantly lower than global seagrass averages. Through isotopic analysis we found that the majority of the carbon originated from noneelgrass sources and very little from eelgrass itself. These results, the first to reveal eelgrass carbon sequestration capacities in the Northeastern Pacific, expose the importance of obtaining local values for carbon sequestration. Key Points: Sediment carbon content varied both within and among Northeast Pacific eelgrass meadows, yet there was no clear latitudinal trend Carbon in eelgrass meadow sediments appears to be derived largely from noneelgrass sources Northeast Pacific carbon stocks and accumulation rates are comparable to other Z. marina meadows but lower than global seagrass values